Global marketing and advertising - Mooij, Marieke K. de (SAGE, 2010)
The paradoxes in global marketing communications -- Global branding -- Values and culture -- Dimensions of culture -- Culture and consumer behavior -- Researching and applying cultural values -- Culture and communication -- Culture and the media -- Culture and advertising appeals -- Culture and executional style -- From value paradox to strategy.; Includes bibliographical references and index